2018
DOI: 10.1038/s41467-017-02672-0
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inducing kinase is a therapeutic target for systemic lupus erythematosus

Abstract: NF-κB-inducing kinase (NIK) mediates non-canonical NF-κB signaling downstream of multiple TNF family members, including BAFF, TWEAK, CD40, and OX40, which are implicated in the pathogenesis of systemic lupus erythematosus (SLE). Here, we show that experimental lupus in NZB/W F1 mice can be treated with a highly selective and potent NIK small molecule inhibitor. Both in vitro as well as in vivo, NIK inhibition recapitulates the pharmacological effects of BAFF blockade, which is clinically efficacious in SLE. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 72 publications
(86 reference statements)
3
88
0
Order By: Relevance
“…We hypothesized that these caspase-8-independent phenotypes were due to aberrant activation of the non-canonical NF-kB pathway, as indicated by the processing of NF-kB2 p100 into p52 ( Figure 4A). R26-CreER T2 cIap1 À/À cIap2 fl/fl Ripk3 À/À Casp8 À/À mice dosed with a NIK inhibitor (Brightbill et al, 2018) before and during tamoxifen treatment contained more p100 and less p52 in the large intestine, consistent with a degree of pathway inhibition ( Figure 4B). Neutrophils in the spleen (Figures 4C, 4D, and S4D) and IL-12p40 and IL-10 in the serum ( Figure 4E) were now reduced.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 61%
“…We hypothesized that these caspase-8-independent phenotypes were due to aberrant activation of the non-canonical NF-kB pathway, as indicated by the processing of NF-kB2 p100 into p52 ( Figure 4A). R26-CreER T2 cIap1 À/À cIap2 fl/fl Ripk3 À/À Casp8 À/À mice dosed with a NIK inhibitor (Brightbill et al, 2018) before and during tamoxifen treatment contained more p100 and less p52 in the large intestine, consistent with a degree of pathway inhibition ( Figure 4B). Neutrophils in the spleen (Figures 4C, 4D, and S4D) and IL-12p40 and IL-10 in the serum ( Figure 4E) were now reduced.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 61%
“…Interestingly, our analysis predicted increased nuclear factor-kB pathway activity in LN and it has been shown that selective inhibition of nuclear factor-kB inducing kinase reduces disease severity in an LN mouse model. 46 Furthermore, we predicted increased phosphoinositide 3-kinase activity in FSGS and a human causing FSGS mutation in the anilin gene was shown to increase phosphoinositide 3-kinase activity in podocytes. 47 We also used a signature-matching algorithm to explore potential drugs that could revert the disease phenotype.…”
Section: Resultsmentioning
confidence: 93%
“…MiRNAs (as: miR-155, miR-663a/miR-423-5p, and Let-7) are well represented in both nuclear factor (NF)-κB and IFN-γ causing LN (Honarpisheh, Köhler, von Rauchhaupt, & Lech, 2018). NF-κB can induce inflammation and fibrosis in LN by regulating the transcription of proinflammatory cytokines (Brightbill et al, 2018). Klotho regulates NF-κB activation and participates in protecting the kidneys by mitigating oxidative stress (Zou, Wu, He, Ma, & Gao, 2018).…”
Section: Resultsmentioning
confidence: 99%